2009
DOI: 10.1159/000261898
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive Olive Oil Consumption Is Associated with Lower Likelihood of Developing Left Ventricular Systolic Dysfunction in Acute Coronary Syndrome Patients: The Hellenic Heart Failure Study

Abstract: Background/Aims: The aim of the present work was to evaluate the association between exclusive olive oil consumption and the development of left ventricular systolic dysfunction (LVSD) in patients with a previous acute coronary syndrome (ACS). Methods: From 2006 to 2007, 651 consecutive ACS patients were enrolled. In 288 males (64 ± 13 years) and 75 females (71 ± 11 years), LVSD (ejection fraction <40%) developed after the cardiac event, and 221 males (62 ± 11 years) and 69 females (66 ± 11 years) were without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
0
6
0
1
Order By: Relevance
“…Oxidative stress 25 and inflammation 26 accompany HF, and olive oil, in particular, has been associated with reduced HF risk. 27 Earlier PREDIMED reports showed that biomarkers of inflammation 28 and oxidation 12 were reduced with the MedDiet + EVOO compared with the other two groups. In the current analyses, the difference in the size of the association with HF incidence between the MedDiet + EVOO and MedDiet + nuts groups (although both not significant) might have resulted from the fact that participants in the MedDiet + EVOO group were provided (at no cost) with EVOO with a highly constant content of polyphenols.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Oxidative stress 25 and inflammation 26 accompany HF, and olive oil, in particular, has been associated with reduced HF risk. 27 Earlier PREDIMED reports showed that biomarkers of inflammation 28 and oxidation 12 were reduced with the MedDiet + EVOO compared with the other two groups. In the current analyses, the difference in the size of the association with HF incidence between the MedDiet + EVOO and MedDiet + nuts groups (although both not significant) might have resulted from the fact that participants in the MedDiet + EVOO group were provided (at no cost) with EVOO with a highly constant content of polyphenols.…”
Section: Discussionmentioning
confidence: 95%
“…Several mechanisms might explain a potential beneficial role of the MedDiet for HF prevention, as suggested by our exploratory meta‐analysis, including the MedDiet's anti‐inflammatory and antioxidant properties. Oxidative stress and inflammation accompany HF, and olive oil, in particular, has been associated with reduced HF risk . Earlier PREDIMED reports showed that biomarkers of inflammation and oxidation were reduced with the MedDiet + EVOO compared with the other two groups.…”
Section: Discussionmentioning
confidence: 98%
“…Of the overall dietary pattern, only consumption of vegetables, salads and nuts was associated with lower risk of recurrent cardiac events (including HF) ( 73 ) . A cross-sectional study by the same group reported that fish, olive oil, pasta and moderate alcohol were associated with improved echocardiography parameters ( 74 ) . In contrast, the MedDiet was not associated with HF risk in multivariate analysis in a separate prospective study ( 75 ) .…”
Section: Resultsmentioning
confidence: 99%
“…Infarct size determines postinfarction survival and prognosis, as it is the most important factor of ventricular remodelling process and left ventricular systolic function. Olive oil, which is the main source of fat in the Mediterranean type of diet, is rich in oleuropein, which has been shown to reduce the infarct size, in experimental models [39,40], and also to protect reperfused myocardium from oxidative damage "in vivo," resulting in more preserved left ventricular systolic function [41]. In a recent study [9], it was revealed that ACS patients that had closer adherence to the Mediterranean diet preserved left ventricular systolic function, while they showed less in-hospital deaths and cardiovascular events during the two-years of followup.…”
Section: Discussionmentioning
confidence: 99%